Frequent HRAS Mutations in Malignant Ectomesenchymoma: Overlapping Genetic Abnormalities With Embryonal Rhabdomyosarcoma. (July 2016) - Huang, Shih-Chiang; Alaggio, Rita; Sung, Yun-Shao; Chen, Chun-Liang; Zhang, Lei; Kao, Yu-Chien; Agaram, Narasimhan P.; Wexler, Leonard H.; Antonescu, Cristina R.
Abstract : Malignant ectomesenchymoma (MEM) is an exceedingly rare pediatric sarcoma with a predilection for infants and young children and is composed of dual malignant mesenchymal and neuroectodermal components. Microscopically, MEM displays areas of rhabdomyosarcoma (RMS) with intermixed neuronal/neuroblastic foci. The molecular alterations associated with MEM and its relationship with embryonal RMS (ERMS) and malignant peripheral nerve sheath tumor (MPNST) have not yet been elucidated. In this study we used whole-transcriptome sequencing in 2 MEM index cases with available frozen tissue, followed by screening of the identified genetic abnormalities in 5 additional cases. No candidate fusion genes were detected by FusionSeq analysis; however, the mutation detection algorithms revealed HRAS and PTPRD hotspot mutations in both index cases, with 1 case harboring an additional FBXW7 mutation. As these mutation profiles have been previously described in ERMS we have tested their incidence in a control group of 7 age-matched ERMS. In addition, the gene signature of MEM was compared with that of RMS, MPNST, and neuronal lineage. All 7 MEM patients were male, with a mean age of 7.5 months (range, 0.6 to 17 mo). All except 1 occurred in the pelvic/urogenital region. Most cases showed ERMS elements, with occasional spindle or undifferentiated/round cell areas. The intermixed neuroectodermal components were mostly scattered ganglion cells, ganglioneuroma, or ganglioneuroblastoma. By Sanger sequencing, 6 of 7 (86%) MEMs had HRAS mutations, with no additional case harboring PTPRD or FBXW7 mutations. The only case lacking HRAS mutation showed neuroblastic micronodules without ganglion cells. The trimethylation at lysine 27 of histone H3 (H3K27me3) expression, typically lost in MPNST, was retained in all cases. In the control ERMS group, 5 of 7 (71%) showed RAS mutations, equally distributed among NRAS, KRAS, and HRAS genes. The expression profiling of MEM showed upregulation of skeletal muscle and neuronal genes, with no significant overlap with MPNST. Our results of common HRAS mutations and composite gene signature with RMS and neuronal/neuroblastic elements suggest a closer genetic link of MEM to RMS rather than to MPNST. Abstract : Supplemental Digital Content is available in the text.